Scoping Review: Obstacles in Implementing Supplementary Food Program for Pregnant Women - Erni Yuliati; Ayun Sriatmi; Antono Suryoputro (GLOBAL HEALTH SCIENCE GROUP, 2024)
The percentage of pregnant women with Chronic Energy Deficiency (CED) in Indonesia is still quite high. This will give a negative impact on the mother’s and baby’s health. Indonesian government overcomes the problem of CED pregnant women through the provision of supplementary food. The identified obstacles in implementing supplementary food program for pregnant women can be used as consideration in planning, implementation, monitoring and reporting at the Community Health Center. The method used in this study is scoping review. Article identification uses two databases, namely Google Scholar and Garuda. The article searched in the database was 919 articles. After screening with inclusion and exclusion criteria, there were 7 eligible articles. In the input aspect, deficiencies were found in the quantity and quality of health human resources, funds and facilities. In the process aspect, the distribution of PMT from the center was uncertain and there was no monitoring of the use of PMT by the target. Some CED pregnant women were also less compliant in taking PMT and consuming PMT. In the output aspect, the system of program’s monitoring and evaluation at the Community Health Center was not carried out well.